2019
DOI: 10.1016/j.lindif.2019.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Predicting educational attainment: Does grit compensate for low levels of cognitive ability?

Abstract: This study examined the role of cognitive ability in moderating grit's predictive effect on educational outcomes. Using a large, representative sample of young adults, we estimated multivariate regression models for the probability of graduating from high school, enrolling in college, earning any college degree, and earning a college degree. For each outcome, the effect of grit (and, alternatively, consistency of interest and perseverance of effort) was allowed to differ for students in each quartile of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 56 publications
0
14
0
1
Order By: Relevance
“…Research on grit has also revealed differentiated effects for low-and high-ability students. In demanding situations, low-ability students substitute their ability with a higher level of grit, while high-ability students' ability is complemented by grit (Light & Nencka, 2019). These findings indicate that grit might be more valuable in circumstances of adversity, and across different subgroups.…”
Section: Group Differences In Gritmentioning
confidence: 85%
See 1 more Smart Citation
“…Research on grit has also revealed differentiated effects for low-and high-ability students. In demanding situations, low-ability students substitute their ability with a higher level of grit, while high-ability students' ability is complemented by grit (Light & Nencka, 2019). These findings indicate that grit might be more valuable in circumstances of adversity, and across different subgroups.…”
Section: Group Differences In Gritmentioning
confidence: 85%
“…The literature shows that grit is associated with range of positive factors including academic effort (e.g., time spent on practice) learning outcomes (Duckworth et al, 2011), high-school graduation (Light & Nencka, 2019), retention (Eskreis-Winkler et al, 2014), academic performance (Li et al, 2018) and student well-being (Datu et al, 2016;Disabato et al, 2019;Vaino & Daukantaitè, 2016). Findings suggest that grittier individuals are better able to use their capabilities, find it easier to engage in extended learning practices, and are less likely to be distracted (Duckworth et al, 2011).…”
Section: Gritmentioning
confidence: 99%
“…In a metaanalysis, Credé et al (2017) showed that the relationship between grit and school performance was weak when it was modulated by other variables that grit is strongly related to, such as conscientiousness (Fite et al, 2017;Ivcevic & Brackett, 2014;Schmidt et al, 2018), selfefficacy (Usher et al, 2019), and self-control (Muenks et al, 2017). Nonetheless, many studies have found higher levels of grit to be related to better academic performance in university students (Akos & Kretchman, 2017;Bowman et al, 2015;Eskreis-Winkler et al, 2014;Fong & King, 2019;Hwang et al, 2018;Muenks, et al, 2017;Muenks et al, 2018), high school students (Duckworth & Quinn, 2009;Muenks et al, 2017Muenks et al, , 2018Steinmayr et al, 2018), and middle school students (Clark & Malecki, 2019;Dumfart & Neubauer, 2016;Hagger & Hamilton, 2018;Malanchini et al, 2018;Steinmayr et al, 2018;Tucker-Drob et al, 2016), and that grit plays a mediating role in the performance of students with low cognitive ability (Light & Nencka, 2019). Nonetheless, most of the work has been carried out with students in the USA, and few studies have been carried out in Europe (Dumfart & Neubauer, 2016;Steinmayr et al, 2018).…”
Section: Article In Pressmentioning
confidence: 99%
“…Another aspect to highlight is that it might be interesting for future research to consider students' cognitive capacity, given its significance in school performance (Chamorro-Premuzic & Furnham, 2004;Heckman & Kautz, 2012;Rosander & Backstrom, 2014). In this way, the extent of academic grit's mediating role may be studied, over time, based on the students' intellectual capabilities (Light & Nencka, 2019). Finally, it is important to reiterate that our results were obtained for a very specific age range (10-14), and so caution is advised when generalizing to other ages.…”
Section: Article In Pressmentioning
confidence: 99%
“…One of the goals of contemporary physical education is also to prepare students for long lasting physical activity. Although several researchers (Cosgrove, Chen, & Castelli, 2018;Larkin, O'Connor, & Williams, 2016) have demonstrated the positive effect of grit on different behavioural domains, including education (Sturman & Zappala-Piemme, 2017;Light & Nencka, 2019;Collaco, 2018;Wang & Baker, 2018), there is limited understanding of the impact of personality trait, such as grit, on student engagement and outcomes in respect of physical activity (Wang & Degol, 2014). Moreover, there is a lack of studies that have examined the independent effects of grit on physical education outcomes, such as objectively measured leisure-time physical activity.…”
Section: Introductionmentioning
confidence: 99%